Collective Bargaining Results - Smith, Douglas (Relations industrielles / Industrial Relations, 1970)
The author of the following article discusses the relation-ship between inflation and collective bargaining. Collective bargaining cannot in a vacuum create inflationary wage increases. Rather, it is the interaction of mark-up or target-return pricing and profit-based wage demands that sets off the spiral of discretionary increases in wages and prices. In the author's opinion, it would be necessary to strive for intelligent methods of reducing the conflict between good industrial relations and a stable price level or face the consequences of the actions of those who seek to impose un-workable controls on the collective bargaining system.